(untitled) (Eduscotech, 2022)
The problem of this research is the low mastery of educators on pedagogical competence and professional competence. The purpose of the research is to describe pedagogical competence and professional competence for mapping the quality of educators based on the condition of educator competence at SDN Pesu 2. This research uses a qualitative method. The sources of the research are educators, students and principals. The subjects in this study were educators at SDN Pesu 2. Data collection techniques in this study were observation, interviews, and documentation. The results of this study indicate that the mastery of pedagogical competence and professional competence to improve the quality of educators is less than optimal, considering the conditions, further optimization of actions is still needed to improve the quality of educators at SDN Pesu 2.